2016
DOI: 10.1016/j.celrep.2015.12.024
|View full text |Cite
|
Sign up to set email alerts
|

A Dendritic Golgi Satellite between ERGIC and Retromer

Abstract: The local synthesis of transmembrane proteins underlies functional specialization of dendritic microdomains in neuronal plasticity. It is unclear whether these proteins have access to the complete machinery of the secretory pathway following local synthesis. In this study, we describe a probe called pGolt that allows visualization of Golgi-related organelles for live imaging in neurons. We show that pGolt labels a widespread microsecretory Golgi satellite (GS) system that is, in contrast to Golgi outposts, pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
119
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(130 citation statements)
references
References 35 publications
8
119
0
Order By: Relevance
“…It is currently not clear whether the glycan composition of NMDARs is modified in the somatic GA, at dendritic Golgi outposts, and/or at Golgi satellite structures (Mikhaylova et al . ). Nevertheless, it has been suggested that unlike α‐amino‐3‐hydroxy‐5‐methyl‐4‐isoxazolepropionic acid (AMPA) receptors, NMDARs may bypass the somatic GA during their journey to the synapse (Jeyifous et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It is currently not clear whether the glycan composition of NMDARs is modified in the somatic GA, at dendritic Golgi outposts, and/or at Golgi satellite structures (Mikhaylova et al . ). Nevertheless, it has been suggested that unlike α‐amino‐3‐hydroxy‐5‐methyl‐4‐isoxazolepropionic acid (AMPA) receptors, NMDARs may bypass the somatic GA during their journey to the synapse (Jeyifous et al .…”
Section: Discussionmentioning
confidence: 97%
“…Consistent with this notion, the necessary glycosylation machinery is also present in dendrites of hippocampal neurons (Torre and Steward ; Mikhaylova et al . ); thus, it is conceivable that all Golgi systems can be used for processing N ‐glycans on NMDARs. Based on their sensitivity to Endo H, AMPARs and kainate receptors have clearly distinguishable pools of immature and mature forms (Standley et al .…”
Section: Discussionmentioning
confidence: 99%
“…This process is regulated by a RhoA-ROCK signaling pathway that activates two Golgi-localized kinases, protein kinase D1 (PKD1) and LIM domain kinase 1 (LIMK1), to promote tubule fission [91*]. In addition to outposts, dendrites further contain Golgi satellites, which represent simplified secretory micro-compartments that, in contrast to Golgi outposts, are seemingly deprived of essential Golgi proteins functioning in sorting and structural organization [92]. Whether these secretory units are indeed Golgi elements derived from the somatic ribbon, their exact ultrastructure and how they relate to Golgi outposts await further clarification.…”
Section: Morphological Variations Of the Golgi Ribbon During Differenmentioning
confidence: 99%
“…Larger GO (>1 um), localized to first- or second-order segments of major dendrites; smaller GO (0.3–1 um) preferentially localized to second-order and greater segments of major dendrites and in minor dendrites (Quassollo et al 2015). Mikhaylova et al (2016) showed that GS have a separate function from GO, have a somatic Golgi origin, contain glycosylation machinery, and are in close association with dendritic ER-Golgi intermediate compartments (ERGIC) (Mikhaylova et al 2016). Further biogenic analysis of GO and GS is necessary to determine if these are indeed separate organelles.…”
Section: Golgi Apparatus In Neuronsmentioning
confidence: 99%
“…Via an unidentified sorting process, proteins could exit the ER/cis-Golgi, without completely traversing the Golgi, and produce fully functional receptors (Hanus et al 2016; Jeyifous et al 2009). Although GO and GS contain glycosylation enzymes and polysialylated proteins (Mikhaylova et al 2016), it is not yet known if proteins that avoid traditional Golgi trafficking pathways are modified in GO and GS.…”
Section: Golgi Trafficking and Glycosylation In Neuronsmentioning
confidence: 99%